Sugarcane radiation use efficiency: varietal differences, temperature dependence, and implications for modeling biomass across environments - (:unkn) unknown (My University, 2025)
Sugarcane is a major tropical C4 crop of global economic significance, primarily used for sugar, ethanol, and bioenergy production. As climate change accelerates, with projected increases in global temperatures, understanding the temperature sensitivity of sugarcane's radiation use efficiency (RUE) is crucial for predicting yield under changing environmental conditions. This study aimed to characterize sugarcane RUE response to temperature across various environments and varieties from key producing regions worldwide. Using experimental data from six countries (Brazil, South Africa, United States of America, Zimbabwe, Argentina, and La Réunion) and 40 distinct varieties, our results indicated that maximum RUE (RUEMAX) remained consistent across varieties, while apparent RUE (RUEA) showed significant variation. Based on this dataset, we parameterized different RUEMAX temperature response formalisms used in crop models (APSIM-Sugar, DSSAT-Canegro, MOSICAS, and emergent formalisms). We compared their ability to simulate RUEA in various regions accurately. Our analysis revealed significant differences in formalism performance, emphasizing the need for accurate parameterization. Additionally, we demonstrated that predictions of biomass production under climate change scenarios are highly sensitive to the formalism parameterization used to represent the RUE-temperature relationship. These findings highlight the critical importance of refining crop models considering temperature response and cardinal temperatures (optimal range: 30–33 °C) to enhance predictions of sugarcane yield under future climate conditions. We discussed several physiological processes that may explain differences in RUEA among varieties. Incorporating these refined mechanisms into models will support more accurate climate impact assessments and aid breeding programs focused on developing high-yield sugarcane varieties.
Keywords: African Research